2020
DOI: 10.1115/1.4048228
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Performance, Combustion, and Emission Characteristics of Spark-Ignition Engine Fueled With 2,5-Dimethylfuran Compared to Ethanol and Gasoline

Abstract: Currently, the supply of diminishing fossil fuel reserves, and the rise in challenges in environmental, political and economic consequences have caused the great concerns in the development of modern society, these have been forced the policy makers and researchers to look for the renewable and green energy sources. Deemed as a promising renewable alternative to traditional fossil fuels, 2,5-dimethylfuran (DMF, chemical formula C6H8O) – a derivative of furan – has the potential to relieve the growing shortage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 135 publications
1
2
0
Order By: Relevance
“…Due to the rich content of oxygen, high ratio of stoichiometric air/fuel, low sulfur content, and high ratio of hydrogen/carbon, the concentration of emission are declined. Some similar discussions have also been shown in the comparative studies using the DMF additive by Tran et al (Tran et al, 2021) (Chan, 2018) and Bui et al (Balasubramanian et al, 2021a). Moreover, findings from the study by Akcay et al (Akcay and Ozer, 2019) observed that the use of fusel oil mixtures declined CO, NOx, and smoke emissions.…”
Section: Impact Of Alcohol Additives On Emission Characteristicssupporting
confidence: 68%
“…Due to the rich content of oxygen, high ratio of stoichiometric air/fuel, low sulfur content, and high ratio of hydrogen/carbon, the concentration of emission are declined. Some similar discussions have also been shown in the comparative studies using the DMF additive by Tran et al (Tran et al, 2021) (Chan, 2018) and Bui et al (Balasubramanian et al, 2021a). Moreover, findings from the study by Akcay et al (Akcay and Ozer, 2019) observed that the use of fusel oil mixtures declined CO, NOx, and smoke emissions.…”
Section: Impact Of Alcohol Additives On Emission Characteristicssupporting
confidence: 68%
“…Recently, several studies have also confirmed the aptness of DMF for internal combustion engines (ICEs), without the need for further engine modification, suggesting that DMF could be a potential biofuel in the future. In the literature, there are some reviews over the DMF synthesis as well as the use of DMF for ICEs as an alternative fuel.…”
Section: Introductionmentioning
confidence: 99%
“…9Both DMF and MF have been tested in combustion engines due to their high energy density and blending ability, but almost exclusively in gasoline engines due to their low carbon and high octane numbers (119 for DMF and 103 for MF). 15,16 Studies into the use of these as diesel fuel blends are more scarce due to relatively high resistance to autoignitoin. [17][18][19][20] Saturated derivatives are arguably more applicable for diesel engines as it has been shown that these are more prone to autoignition with higher cetane numbers, 15,21,22 although some contradictions to this have been found based on the engine operating conditions.…”
mentioning
confidence: 99%